PERBEDAAN KEMAMPUAN MATEMATIKA CALON MAHASISWA BARU UNIVERSITAS ASAHAN BERDASARKAN JENIS KELAMIN - Zuriah Sitorus (Delta: Jurnal Ilmiah Pendidikan Matematika, 2013)
The research aimed to determine the differences in test results of matriculants of Asahan University that were based on gender. To achieve these objectives, the research took samples by gender and school of origin. The results of hypothesis testing showed that women matriculants had better test results than the men. This was evidenced by tcount = 2.76> ttable = 2.01 at significance level α = 0.05.